Composite material and preparation method thereof, light-emitting device and display device

By attaching long-chain ligands with multiple unsaturated bonds to inorganic semiconductor particles, the composite material addresses the unbalanced electron and hole injection in semiconductor materials, enhancing film formation and device performance in OLEDs.

CN119709202APending Publication Date: 2025-03-28GUANGDONG JUHUA RES INST OF ADVANCED DISPLAY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311279197.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Noine semiconductor materials face issues with unbalanced electron and hole injection performance due to aggregation, which affects the film formation and overall efficiency of semiconductor devices.

Method used

A composite material is developed by attaching specific long-chain ligands with multiple unsaturated bonds to the surface of inorganic semiconductor particles, improving dispersion and reducing inter-particle transition barriers, thereby enhancing electron and hole injection capabilities.

Benefits of technology

The approach results in improved film formation, increased quantum efficiency, and prolonged device lifespan by balancing electron and hole injection, leading to higher luminance and external quantum efficiency in OLEDs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709202A_ABST
    Figure CN119709202A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material and a preparation method thereof, a luminescent device and a display device, the composite material comprises inorganic semiconductor particles and ligands connected to the inorganic semiconductor particles, and the raw materials of the ligands have the following structural formula: R1-R2, wherein R1 is a substituted or unsubstituted C8-C24 unsaturated chain alkyl group, and the R1 contains two or more than two unsaturated bonds; r2 is a binding group connected with the inorganic semiconductor particles; the substituent group comprises one or more of C1-C5 alkoxy, halogen, sulfydryl, amino, phosphonic acid group, carboxyl and thiocarboxylic acid group. The invention aims to solve the problem that the electron injection performance and the hole injection performance of an inorganic semiconductor material are unbalanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of semiconductors, and in particular to a composite material and a preparation method thereof, a light-emitting device and a display device. Background Art

[0002] Inorganic semiconductor materials refer to inorganic materials with semiconductor properties. Currently commonly used inorganic materials, such as cadmium sulfide nanoparticles, cadmium selenide nanoparticles, zinc oxide nanoparticles, molybdenum oxide nanoparticles, tungsten oxide nanoparticles, molybdenum sulfide nanoparticles, etc., are widely used in semiconductor devices due to their suitable energy levels and excellent carrier injection or transport properties.

[0003] Inorganic semiconductor materials tend to aggregate with each other, which affects their film-forming effect. In view of this, ligands are usually attached to the surface of inorganic semiconductor materials to improve their dispersibility. At present, common ligands include oleic acid, oleylamine, etc. However, after attaching these ligands, inorganic semiconductor materials often have the problem of unbalanced electron injection performance and hole injection performance. Summary of the invention

[0004] In view of this, the present application provides a composite material and a preparation method thereof, a light-emitting device and a display device, aiming to solve the problem of unbalanced electron injection performance and hole injection performance of inorganic semiconductor materials.

[0005] The embodiment of the present application is implemented as follows:

[0006] In a first aspect, the present application provides a composite material, comprising inorganic semiconductor particles and ligands connected to the inorganic semiconductor particles, wherein the raw material of the ligand has the following structural formula:

[0007] R1-R2;

[0008] Wherein, R1 is a substituted or unsubstituted C8-C24 unsaturated chain hydrocarbon group, said R1 contains two or more unsaturated bonds, and said substituted substituent includes one or more of C1-C5 alkyl, C1-C5 alkoxy, halogen, thiol, amino, phosphonic acid group, carboxyl, and thiocarboxylic acid group;

[0009] R2 is a bonding group connected to the inorganic semiconductor particles.

[0010] Optionally, in some embodiments of the present application, in R1, two adjacent unsaturated bonds are separated by N carbon-carbon single bonds, where N is an integer greater than or equal to 2; and / or,

[0011] In said R1, said unsaturated bond is a carbon-carbon double bond; and / or,

[0012] In the R1, the number of the unsaturated bonds is 3 to 6; and / or,

[0013] The R2 is a mercapto group, an amino group, a carboxyl group, a phosphonic acid group or a thiocarboxylic acid group.

[0014] Optionally, in some embodiments of the present application, the R1 is selected from -(CH2) n1 (CH2CH=CH) n2 (CH2) n3 CH3, wherein n1 is greater than or equal to 0, n2 is 3 to 6, n3 is greater than or equal to 0, and n1+n3 is 0 to 10; and / or,

[0015] The R2 is a phosphonic acid group or a thiocarboxylic acid group.

[0016] Optionally, in some embodiments of the present application, the raw material of the ligand is selected from compounds having a structure shown in any one of the following formulae (A1) to (A9).

[0017]

[0018] Optionally, in some embodiments of the present application, in the composite material, the weight percentage of the ligand is 5-20%; and / or,

[0019] The inorganic semiconductor particles include quantum dots, and the quantum dots include at least one of single-structure quantum dots, core-shell quantum dots and perovskite semiconductor materials; the material of the single-structure quantum dots, the core material of the core-shell quantum dots and the shell material of the core-shell quantum dots are respectively selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds; the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnS At least one of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, Pb At least one of SeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, Ga At least one of AlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2 + , Cu2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2 + 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

[0020] In a second aspect, the present application also proposes a method for preparing a composite material, comprising the following steps:

[0021] providing inorganic semiconductor particles, organic solvents and ligand sources;

[0022] Mixing the inorganic semiconductor particles, the organic solvent and the ligand source to obtain a composite material, wherein the composite material includes inorganic semiconductor particles and ligands connected to the inorganic semiconductor particles;

[0023] Wherein, the ligand source has the following structural formula: R1-R2, R1 is a substituted or unsubstituted C8-C24 unsaturated chain hydrocarbon group, the substituted substituent includes one or more of C1-C5 alkyl, C1-C5 alkoxy, halogen, thiol, amino, phosphonic acid group, carboxyl, thiocarboxylic acid group, and R1 contains two or more unsaturated bonds;

[0024] R2 is a binding group connected to the inorganic semiconductor particle;

[0025] The substituents include one or more of C1-C5 alkoxy, halogen, mercapto, amino, phosphonic acid, carboxyl, and thiocarboxylic acid groups.

[0026] Optionally, in some embodiments of the present application, the organic solvent includes at least one of aromatic hydrocarbons, olefins, aromatic olefins, aromatic ethers, aromatic esters and C5-18 alkanes; and / or,

[0027] The weight ratio of the inorganic semiconductor particles to the ligand is (4-7):1; and / or,

[0028] In the step of mixing the inorganic semiconductor particles, the organic solvent and the ligand source, the temperature during the mixing is 15 to 50° C.; and / or,

[0029] The ligand source is selected from compounds having a structure represented by any one of the following formulae (A1) to (A9).

[0030]

[0031] Optionally, in some embodiments of the present application, the ligand source includes a first ligand source, in the structure of which R2 is a thiocarboxylic acid group;

[0032] The preparation of the first ligand source comprises:

[0033] providing a first raw material, a first solvent and a Lawesson reagent;

[0034] The first raw material, the first solvent and the Lawesson's reagent are mixed and reacted at 80 to 120° C. to obtain a first ligand source;

[0035] The structure of the first raw material is R3-COOH, wherein R3 is the same as R1 in the structure of the first ligand source.

[0036] Optionally, in some embodiments of the present application, the ligand source includes a second ligand source, in the structure of the second ligand source, R2 is a phosphonic acid group;

[0037] The preparation of the second ligand source comprises:

[0038] Provide a second raw material, N,N′-dicyclohexylcarbodiimide, 2-thiopyridine-N-oxide and a second solvent;

[0039] The second raw material, N,N′-dicyclohexylcarbodiimide, 2-thiopyridine-N-oxide and a second solvent are mixed, and after reaction, solid-liquid separation is performed to obtain an intermediate product;

[0040] Providing a first solution containing phosphorus;

[0041] Provide hydrogen peroxide;

[0042] The intermediate product, the first solution and the hydrogen peroxide are mixed and subjected to a reflux reaction to obtain a second ligand source;

[0043] The structure of the second raw material is R4-CH2COOH, wherein R4 is the same as R1 in the structure of the second ligand source.

[0044] In a third aspect, the present application further proposes a light-emitting device, comprising an anode, a light-emitting layer and a cathode, wherein the material of the light-emitting layer comprises the composite material described above, or comprises the composite material prepared by the preparation method described above.

[0045] Optionally, in some embodiments of the present application, the cathode and the anode are each independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, and the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0046] In a fourth aspect, the present application further proposes a display device, comprising the light-emitting device as described above.

[0047] The present application provides a composite material, which connects long-chain ligands with multiple unsaturated bonds on the surface of inorganic semiconductor particles. On the one hand, the dispersibility of the inorganic semiconductor particles is greatly improved, so that they have a better film-forming effect. On the other hand, the introduction of multiple unsaturated bonds effectively reduces the transition barrier of carriers between inorganic semiconductor particles and inorganic semiconductor particles, which helps to improve the hole injection ability and electron injection ability of the inorganic semiconductor particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0049] Figure 1 is a schematic structural diagram of a light-emitting device proposed in one embodiment of the present application;

[0050] Reference numerals:

[0051] 100 - light-emitting device; 10 - anode; 20 - electron transport layer; 30 - light-emitting layer; 40 - cathode; 50 - hole injection layer; 60 - hole transport layer. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0053] In this application, unless otherwise specified, the directional words used, such as "upper" and "lower", refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of this application, the term "including" means "including but not limited to".

[0054] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0055] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0056] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0057] In a first aspect, an embodiment of the present application provides a composite material, the composite material comprising inorganic semiconductor particles and ligands connected to the inorganic semiconductor particles, wherein the raw material of the ligand has the following structural formula:

[0058] R1-R2;

[0059] Among them, R1 is a substituted or unsubstituted C8~C24 unsaturated chain hydrocarbon group, and R1 contains two or more unsaturated bonds; R2 is a binding group connected to the inorganic semiconductor particle; the substituent includes one or more of C1~C5 alkoxy, halogen, thiol, amino, phosphonic acid group, carboxyl, and thiocarboxylic acid group.

[0060] The "unsaturated chain hydrocarbon group" described in the present application refers to a hydrocarbon group containing an unsaturated bond and being chain-shaped as a whole, which can be an unsaturated branched hydrocarbon group or an unsaturated straight-chain hydrocarbon group. The number of carbon atoms in the unsaturated chain hydrocarbon group can be 8 to 24, 8 to 12, 10 to 15, 13 to 18, 16 to 22, 20 to 24, and the like.

[0061] In the present application, "substituted or unsubstituted" means that the defined group may be substituted or unsubstituted. When the defined group is substituted, it should be understood that the defined group may be substituted by one or more substituents, and the substituents are selected from but not limited to one or more of C1-C5 alkyl, C1-C5 alkoxy, halogen, sulfhydryl, amino, phosphonic acid group, carboxyl, thiocarboxylic acid group.

[0062] In the present application, alkoxy refers to -OR, wherein R refers to a branched alkyl group or a straight-chain alkyl group; halogen refers to -I, -Br, -Cl or -F; mercapto refers to -SH; amino refers to -NH2; phosphonic acid group refers to -PO3; carboxyl refers to -COOH; thiocarboxylic acid group refers to or

[0063] In some embodiments, the inorganic semiconductor particles include quantum dots, and the quantum dots include at least one of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials; the material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots are respectively selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds; the II-VI group compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSe At least one of CdS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe , SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs , AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2.

[0064] As an example, the core-shell structured quantum dots may be selected from but not limited to at least one of CdZnSe / CdZnSe / ZnSe / CdZnS / ZnS, CdZnSe / CdZnSe / CdZnS / ZnS CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS.

[0065] It should be noted that, for the material of the aforementioned single structure quantum dot, or the material of the core of the core-shell structure quantum dot, or the material of the shell of the core-shell structure quantum dot, the chemical formula provided only indicates the elemental composition, but does not indicate the content of each element. For example, CdZnSe only indicates that it is composed of three elements, Cd, Zn and Se. If the content of each element is indicated, it corresponds to Cd x Zn 1-x Se,0 <x<1。

[0066] The perovskite semiconductor material may be selected from but not limited to doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

[0067] In the composite material provided in the present application, the surface of the inorganic semiconductor particles is connected with a ligand derived from R1-R2, and the ligand is bound to the surface of the inorganic semiconductor particles through R2. The ligand is a long-chain ligand, which greatly improves the dispersibility of the inorganic semiconductor particles and enables it to have a better film-forming effect.

[0068] In some embodiments, the composite material can be used to make the light-emitting layer 30 of the light-emitting device 100. After film formation, the ligand is approximately curled up and wrapped around the inorganic semiconductor particles. When the device is working, the carriers (electrons and holes) in the light-emitting layer 30 need to transition from the ligand on the surface of one inorganic semiconductor particle to the ligand on the surface of another particle, and then enter the interior of the particle. The presence of delocalized electrons in unsaturated bonds will reduce the transition barrier of carriers, which is beneficial to carrier injection and the efficiency of carrier transition between inorganic semiconductor particles; the ligand has multiple unsaturated bonds, and the introduction of multiple unsaturated bonds effectively reduces the transition barrier of carriers between inorganic semiconductor particles and inorganic semiconductor particles, which helps to improve the hole injection ability and electron injection ability of inorganic semiconductor particles. When the composite material is used to prepare the light-emitting layer 30, it is beneficial to reduce the transition barrier of carriers between quantum dots, between the hole transport layer 60 and the light-emitting layer 30, and between the electron transport layer 20 and the light-emitting layer 30, and improve the injection capacity of quantum dot holes and electrons, thereby improving the brightness of the QLED device; and because the improvement in hole injection capacity is relatively more significant, it also helps to improve the carrier balance of the device, thereby extending the service life and EQE of the device.

[0069] In some embodiments, in the R1, two adjacent unsaturated bonds are separated by N carbon-carbon single bonds, where N is an integer greater than or equal to 2; that is, the ligand in this embodiment is a non-conjugated ligand, and the multiple unsaturated bonds it contains do not constitute a conjugated system. When the ligand is a non-conjugated ligand, the light-emitting device 100 has a relatively higher EQE in a low electric field environment.

[0070] In some embodiments, in R1, the unsaturated bond is a C=C carbon-carbon double bond.

[0071] In some embodiments, in the R1, the number of the unsaturated bonds is 3 to 6; for example, it may contain 3, 4, 5 or 6 unsaturated bonds.

[0072] In some embodiments, the R2 is a sulfhydryl group, an amino group, a carboxyl group, a phosphonic acid group or a thiocarboxylic acid group. It should be noted that a "binding group" refers to a group that has the ability to bind, and there are many ways to bind. For example, when R2 is a carboxyl group, a phosphonic acid group or a thiocarboxylic acid group, the ligand raw material interacts with the inorganic semiconductor particles and binds, and its binding state is a carboxylic acid metal salt, a thiocarboxylic acid metal salt or a phosphonic acid metal salt (the metal ion is a metal ion on the surface of the inorganic semiconductor particle); when R2 is a sulfhydryl group or an amino group, a coordination bond is formed between the R2 of the ligand raw material and the uncoordinated metal ion on the surface of the inorganic semiconductor particle.

[0073] In other embodiments, R2 is a phosphonic acid group or a thiocarboxylic acid group, which helps to improve the binding ability between the ligand and the inorganic semiconductor particles, reduce the damage to the binding caused by the external environment (such as ultraviolet light irradiation, oxygen corrosion, etc.), reduce the ligand shedding, and help improve the stability of the quantum dots.

[0074] In some embodiments, the R1 is selected from -(CH2) n1 (CH2CH=CH) n2 (CH2) n3 CH3; wherein n2 is 3 to 6, for example, 3, 4, 5 or 6; wherein n1 is greater than or equal to 0, n3 is greater than or equal to 0, and n1+n3 is 0 to 10, for example, n1=0, n3=1; n1=1, n3=2; n1=2, n3=3; n1=4, n3=5; n1=6, n3=4; n1=5, n3=1; n1=6, n3=0; n1=2, n3=0; and so on.

[0075] In some embodiments, the ligand is selected from compounds having a structure represented by any one of the following formulae (A1) to (A9).

[0076]

[0077] In some embodiments, in the composite material, the weight percentage of the ligand is 5-20%; for example, it can be 5%, 6%, 10%, 12%, 15%, 18%, 20% and values ​​between any two of the above values.

[0078] In a second aspect, the present application also proposes a method for preparing a composite material, the preparation method comprising the following steps:

[0079] S100, providing inorganic semiconductor particles, organic solvent and ligand source;

[0080] S200, mixing the inorganic semiconductor particles, the organic solvent and the ligand source to obtain a composite material, wherein the composite material includes inorganic semiconductor particles and ligands connected to the inorganic semiconductor particles;

[0081] Wherein, the ligand source has the following structural formula: R1-R2, R1 is a substituted or unsubstituted C8~C24 unsaturated chain hydrocarbon group, and R1 contains two or more unsaturated bonds; R2 is a binding group connected to the inorganic semiconductor particle; the substituent includes one or more of C1~C5 alkoxy, halogen, thiol, amino, phosphonic acid group, carboxyl, and thiocarboxylic acid group.

[0082] In step S100:

[0083] In some embodiments, the organic solvent includes at least one of aromatic hydrocarbons, olefins, aromatic olefins, aromatic ethers, aromatic esters, and C5-18 alkanes.

[0084] In some embodiments, the ligand source is selected from compounds having a structure represented by any one of formulae (A1) to (A9).

[0085] The ligand source can be purchased on the market or prepared by itself. In some embodiments, step S100 also includes the preparation of the ligand source. The ligand source is prepared based on an organic carboxylic acid having a similar unsaturated chain hydrocarbon structure. In actual preparation, the ligand source R2 type can be prepared with the corresponding organic carboxylic acid as a raw material according to conventional methods in the art.

[0086] For example, when R2 is a thiocarboxylic acid group, the corresponding ligand source is named the first ligand source. The first ligand source can be a compound having the structure of A1, A3, A5, A7 or A9.

[0087] The preparation of the first ligand source comprises:

[0088] S11, providing a first raw material, a first solvent and a Lawesson reagent;

[0089] S12, mixing the first raw material, the first solvent and the Lawesson's reagent, and reacting them at 80-120° C. to obtain a first ligand source.

[0090] Wherein, the first solvent is selected from but not limited to one or more of dichloromethane, chloroform, and tetrahydrofuran.

[0091] The structure of the first raw material is R3-COOH, wherein R3 is the same as R1 in the structure of the first ligand source. Specifically:

[0092] When the first ligand source is A1, the first raw material can be selected from 7,10,13 cis-hexadecatrienoic acid (structural formula B1), CAS: 7561-64-0;

[0093] When the first ligand source is A3, the first raw material can be selected from cis-4,7,10,13,16,19-docosahexaenoic acid (structural formula B2), CAS: 6217-54-5;

[0094] When the first ligand source is A5, the first raw material can be selected from cis-5,8,11,14,17-eicosapentaenoic acid (structural formula B3), CAS: 10417-94-4;

[0095] When the first ligand source is A7, the first raw material can be selected from docosapentaenoic acid (cis-4,7,10,13,16) (structural formula B4), CBNumber: CB72739796.

[0096] When the first ligand source is A9, the first raw material may be selected from linoleic acid (CAS: 60-33-3).

[0097]

[0098] For another example, when R2 is a phosphonic acid group, the corresponding ligand source is named as the second ligand source. The second ligand source can be a compound having the structure of A2, A4, A6 or A8.

[0099] The preparation of the second ligand source comprises:

[0100] S21, providing a second raw material, N,N′-dicyclohexylcarbodiimide, 2-thiopyridine-N-oxide and a second solvent;

[0101] S22, mixing the second raw material, N,N′-dicyclohexylcarbodiimide, 2-thiopyridine-N-oxide and a second solvent, and performing solid-liquid separation after the reaction to obtain an intermediate product;

[0102] S23, providing a first solution containing phosphorus;

[0103] S24, providing hydrogen peroxide;

[0104] S25, mixing the intermediate product, the first solution and the hydrogen peroxide, and performing a reflux reaction to obtain a second ligand source;

[0105] Wherein, the second solvent is selected from but not limited to one or more of dichloromethane, chloroform, and tetrahydrofuran. The second solution also includes a solvent, and the solvent is selected from but not limited to one or more of dichloromethane, chloroform, and tetrahydrofuran.

[0106] The structure of the second raw material is R4-CH2COOH, wherein R4 is the same as R1 in the structure of the second ligand source. Specifically:

[0107] When the second ligand source is A2, the second raw material can be selected from 7,10,13 cis-hexadecatrienoic acid (structural formula B1);

[0108] When the second ligand source is A4, the second raw material may be selected from cis-4,7,10,13,16,19-docosahexaenoic acid (structural formula B2);

[0109] When the second ligand source is A6, the second raw material may be selected from cis-5,8,11,14,17-eicosapentaenoic acid (structural formula B3);

[0110] When the second ligand source is A8, the second raw material can be selected from docosapentaenoic acid (cis-4,7,10,13,16) (structural formula B4).

[0111] In step S200:

[0112] In some embodiments, the weight ratio of the inorganic semiconductor particles to the ligand is (4-7):1; for example, it can be 4:1, 4.5:1, 5:1, 6:1, 7:1, and values ​​between any two of the above-listed values.

[0113] In some embodiments, in the step of mixing the inorganic semiconductor particles, the organic solvent and the ligand source, the mixing temperature is 15-50°C, for example, it can be 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C and values ​​between any two of the values ​​listed above; the mixing time is 1-8h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h and values ​​between any two of the values ​​listed above.

[0114] In a third aspect, the present application also provides a light emitting device 100, which may be an organic light emitting diode (OLED), a quantum dot light emitting diode (QLED), etc. Figure 1 The light emitting device 100 includes an anode 10, a light emitting layer 30 and a cathode 40. The material of the light emitting layer 30 includes the composite material as described above, or includes the composite material prepared by the preparation method as described above.

[0115] In the composite material provided in the present application, the surface of the inorganic semiconductor particles is connected with a ligand derived from R1-R2, and the ligand is bound to the surface of the inorganic semiconductor particles through R2. The ligand is a long-chain ligand, which improves the dispersibility of the inorganic semiconductor particles. When preparing the light-emitting layer 30, it helps to improve the film-forming effect of the light-emitting layer 30, thereby improving the luminous performance and service life of the device. At the same time, since the ligand introduces multiple unsaturated bonds, the transition barrier of the carrier between the inorganic semiconductor particles and the inorganic semiconductor particles is effectively reduced. When the composite material is used to prepare the light-emitting layer 30, it is beneficial to reduce the transition barrier between the carriers between the quantum dots, between the hole transport layer 60 and the light-emitting layer 30, and between the electron transport layer 20 and the light-emitting layer 30, and improve the injection capacity of the quantum dot holes and electrons, thereby improving the brightness of the QLED device; and because the improvement of the hole injection capacity is relatively more significant, it also helps to improve the carrier balance of the device, thereby extending the service life and EQE of the device.

[0116] In some embodiments, the anode 10 can be an anode 10 for a light-emitting device 100 known in the art, for example, can be selected from but not limited to a doped metal oxide particle electrode, a composite electrode of a metal and a metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of a metal and a metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0117] In some embodiments, the cathode 40 can be a cathode 40 for the light-emitting device 100 known in the art, for example, can be selected from but not limited to a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0118] In some embodiments, the light emitting device 100 further includes an electronic functional layer, which is disposed between the light emitting layer 30 and the cathode 40. The electronic functional layer includes an electron transport layer and an electron injection layer. When the device includes both the electron transport layer 20 and the electron injection layer, the electron injection layer is disposed closer to the cathode 40. The electron transport layer 20 can be prepared using a material with electron transport properties known in the art for use in the light emitting device 100. For example, the material of the electron transport layer 20 includes but is not limited to at least one of metal oxides, doped metal oxides, II-VI semiconductor materials, III-V semiconductor materials and I-III-VI semiconductor materials, the metal oxide is selected from at least one of ZnO, BaO, TiO2, SnO2; the metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2, SnO2, the doping element is selected from at least one of Al, Mg, Li, In, Ga, the II-VI semiconductor material is selected from at least one of ZnS, ZnSe, CdS; the III-V semiconductor material is selected from at least one of InP and GaP; the I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS. The material of the electron injection layer includes but is not limited to at least one of cesium carbonate, cesium fluoride, cesium azide and lithium fluoride.

[0119] In some embodiments, the light emitting device 100 further includes a hole functional layer, and the hole functional layer is disposed between the light emitting layer 30 and the anode 10. The hole functional layer includes a hole transport layer 60 and a hole injection layer 50. When the device includes both the hole transport layer 60 and the hole injection layer 50, the hole injection layer 50 is disposed closer to the anode 10. The hole transport layer 60 can be prepared using a material with hole transport properties known in the art for use in the light emitting device 100. For example, the material of the hole transport layer 60 is not limited to 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4'-tri(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine ... 4',4'-Tris(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(phenylenevinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylenevinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines , 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraaryl benzidine, PEDOT:PSS and its derivatives, poly(N-vinyl carbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenyl benzidine, spiro NPB, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO; the material of the hole injection layer 50 includes but is not limited to at least one of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, PEDOT:PSS doped with s-MoO3 derivatives, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

[0120] It is understandable that the thickness of each layer in the light emitting device 100 is set as needed and is not limited here. In some embodiments, the thickness of the anode 10 is 10-110nm, the thickness of the hole injection layer 50 is 30-100nm, the thickness of the hole transport layer 60 is 20-100nm, the thickness of the light emitting layer 30 is 5-30nm, the thickness of the electron transport layer 20 is 15-80nm, the thickness of the electron injection layer is 15-80nm, and the thickness of the cathode 40 is 10-100nm.

[0121] When there are multiple film layers between the anode 10 and the cathode 40, and the multiple film layers are selected from the light-emitting layer 30, the electron injection layer, the electron transport layer 20, the hole transport layer 60, and the hole injection layer 50, the film layer stacking order of the light-emitting device 100 is the anode 10, the hole injection layer 50, the hole transport layer 60, the light-emitting layer 30, the electron transport layer 20, the electron injection layer, and the cathode 40; it can be understood that the light-emitting device 100 can be an upright device or an inverted device. In some embodiments, the light-emitting device 100 is an upright device, and accordingly, the light-emitting device 100 includes an anode 10, a hole injection layer 50, a hole transport layer 60, a light-emitting layer 30, an electron transport layer 20, an electron injection layer, and a cathode 40 stacked in sequence from bottom to top; in other embodiments, the light-emitting device 100 is an inverted device, and accordingly, the light-emitting device 100 includes a cathode 40, an electron injection layer, an electron transport layer 20, a light-emitting layer 30, a hole transport layer 60, a hole injection layer 50 and an anode 10 stacked in sequence from bottom to top.

[0122] It is understandable that the light emitting device 100 may also be provided with some functional layers conventionally used in the light emitting device 100 to help improve the performance of the light emitting device 100, such as an electron blocking layer, a hole blocking layer, an interface modification layer, etc.

[0123] It can be understood that the materials of each layer of the light emitting device 100 can be adjusted according to the actual requirements of the light emitting device 100 .

[0124] The present application also proposes a method for preparing a light-emitting device 100, which can be used to prepare the light-emitting device 100. The preparation method comprises the following steps:

[0125] S1, providing a first electrode;

[0126] S2, disposing a light-emitting layer 30 on the first electrode;

[0127] S3 , disposing a second electrode on the light emitting layer 30 .

[0128] In steps S1 and S3, the first electrode is selected from one of the anode 10 and the cathode 40, and the second electrode is selected from the other of the anode 10 and the cathode 40. In actual preparation, according to the film layer design of the light-emitting device 100, it is determined whether to prepare the anode 10 or the cathode 40 first. For example, when the light-emitting device 100 is designed with the anode 10 at the bottom layer and the cathode 40 at the top layer, the anode 10 is prepared first, and the first electrode is the anode 10.

[0129] It can be understood that when the light-emitting device 100 also includes functional film layers such as the electron transport layer 20 and the hole transport layer 60, between steps S1 and S2 there is also a step of sequentially preparing other functional film layers according to the design order of the film layers of the light-emitting device 100.

[0130] In actual preparation, each film layer of the light-emitting device 100, such as the anode 10, the light-emitting layer 30, the electronic functional layer, the hole functional layer and the cathode 40, can be prepared by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical plating and solution method, among which the physical plating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion plating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, doctor blade coating, printing, dip-coating, immersion, spraying, roll coating, casting, slit coating, and strip coating.

[0131] In some embodiments, after step S3, the step of packaging the light emitting device 100 is also included. The packaging process can be a common machine packaging or a manual packaging. Preferably, in the packaging process environment, the oxygen content and the water content are both less than 0.1ppm to ensure the stability of the light emitting device 100.

[0132] In a fourth aspect, the present application further proposes a display device, which may be a smart phone, a portable phone, a tablet computer, a personal digital assistant (PDA), a portable multimedia player (Portable Multimedia Player), a television, a game console, a watch-type electronic device, a head-mounted display, a display of a personal computer, a notebook computer, a car navigation system, a car dashboard, a digital camera, a portable camera, an external advertising board, an electro-optical board, a medical device, a detection device, a refrigerator, a washing machine, etc. The display device includes the light-emitting device 100 as described above.

[0133] The technical scheme and technical effects of the present application are described in detail below through specific embodiments and comparative examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.

[0134] Material Example 1

[0135] The composite material of this embodiment includes quantum dots and ligands connected to the surface of the quantum dots, wherein the raw material of the ligands is docosahexaenethiocarboxylic acid, and the weight of the ligands accounts for 12% of the weight of the quantum dots.

[0136] (I) The preparation method of the ligand raw material is as follows:

[0137] Take 10 mL of a 0.1 mol / L dichloromethane solution of docosahexaenoic acid, add 0.55 mmmol Lawesson's reagent, use microwave rapid heating to heat the solution to 100°C and maintain for 10 min, use a chromatographic column to separate and purify the product, the yield is about 80%. Perform a nuclear magnetic resonance test, the nuclear magnetic resonance data are as follows: 1 H NMR (500MHz, Chloroform-d) δ5.62-5.31 (m, 12H), 2.74-2.62 (m, 4H), 2.53 (tt, J=5.6, 1.2Hz, 2H), 2.46-2.31 (m, 8H), 2.06-1.97 (m, 2H), 0.99-0.93 (m, 3H). The H of the thiocarboxylic acid functional group -(C=O)SH is an active hydrogen, and there may be no signal in deuterated chloroform. The product is docosahexenothiocarboxylic acid, and its structure is shown in A3.

[0138] (II) The preparation method of the composite material is as follows:

[0139] (1) Take core-shell quantum dots CdSe / ZnS (purchased from Sigma-Aldrich), which have a luminescent wavelength of 580 nm and have oleic acid ligands attached to the surface.

[0140] (2) dispersing the quantum dots in n-hexane; then, adding the ligand raw material prepared in step (i) at a weight ratio of the ligand raw material to the quantum dots of 1:5.

[0141] (3) After stirring at 25° C. for 6 h, ethanol was added for precipitation, and the precipitate was collected to obtain CdSe / ZnS quantum dots with A3 connected on the surface, which was a composite material.

[0142] (4) The composite material was dispersed in n-octane to prepare a composite material solution with a concentration of 15 mg / mL.

[0143] Material Example 2

[0144] The scheme of this embodiment is basically the same as that of embodiment 1, except that, in this embodiment, the raw material of the ligand is hexadecatriene thiocarboxylic acid; correspondingly:

[0145] In step (1), the product obtained by replacing docosahexaenoic acid with hexadecatrienoic acid is hexadecatrienothiocarboxylic acid, and its NMR data are as follows: 1 H NMR (500MHz, Chloroform-d) δ6.79 (s, 1H), 5.45-5.32 (m, 6H), 2.71 (ddqd, J = 6.0, 4.6, 2.3, 1.0 Hz, 4H), 2.56 (t, J = 7.3 Hz, 2H), 2.07-1.97 (m, 4H), 1.70-1.61 (m, 2H), 1.42-1.29 (m, 4H), 0.96 (td, J = 7.4, 0.7 Hz, 3H). The structure is shown in A1.

[0146] The composite material prepared in step (ii) is CdSe / ZnS quantum dots with Al connected to the surface.

[0147] Material Example 3

[0148] The scheme of this embodiment is basically the same as that of embodiment 1, except that, in this embodiment, the ligand raw material is nonadecapentaenoic acid; correspondingly:

[0149] Step (i) is changed to: Take 1.05mmol of N,N'-dicyclohexylcarbodiimide and 1.05mmol of 2-thiopyridine-N-oxide and dissolve them in 4ml of dichloromethane to obtain a mixed solution; take another 4mL of dichloromethane solution with a concentration of 0.25mol / L eicosapentaenoic acid and slowly add it to the mixed solution at 0°C. After reacting for 90min, the product A is separated and purified by a chromatographic column. After dissolving 1mmol of white phosphorus in 10mL of tetrahydrofuran under argon, product A is added thereto at 0°C, followed by slowly adding 0.33mL of 30% hydrogen peroxide solution, and then the reaction solution is refluxed for 12h. Finally, the aqueous phase is left by rotary evaporation, and 20mL of ethyl acetate is added to extract the product. Its NMR data are as follows: 1 H NMR (500MHz, Chloroform-d) δ5.52-5.32 (m, 10H), 2.71 (dtdt, J = 5.3, 4.4, 2.4, 1.1Hz, 4H), 2.46-2.38 (m, 4H), 2.17-2.09 (m, 2H), 2.06-1.87 (m, 4H), 1.84-1.72 (m, 2H), 0.96 (td, J = 7.4, 0.7Hz, 3H). The H in the two -OH of the phosphonic acid functional group is active hydrogen, and there may be no signal in deuterated chloroform. The product is nonadecapentaenoic acid, and its structure is shown in A6.

[0150] The composite material prepared in step (ii) is CdSe / ZnS quantum dots with A6 connected on the surface.

[0151] Material Example 4

[0152] The scheme of this embodiment is basically the same as that of embodiment 3, except that, in this embodiment, the ligand raw material is hexanehexaenoic acid; correspondingly:

[0153] In step (1), the product obtained by replacing eicosapentaenoic acid with docosahexaenoic acid is heneicosahexenoic acid, and its NMR data are as follows: 1 H NMR (500 MHz, Chloroform-d) δ 5.56-5.31 (m, 12H), 2.71 (tp, J = 5.7, 1.3 Hz, 2H), 2.49-2.39 (m, 8H), 2.17-2.02 (m, 4H), 1.97-1.87 (m, 2H), 1.84-1.72 (m, 2H), 0.96 (td, J = 7.4, 1.0 Hz, 3H). The structure is shown in A4.

[0154] The composite material prepared in step (ii) is CdSe / ZnS quantum dots with A4 connected on the surface.

[0155] Material Example 5

[0156] The scheme of this embodiment is basically the same as that of Embodiment 1, with the only difference being that, in this embodiment, in step (ii), the quantum dots are changed to CdZnSeS / ZnS; accordingly, the obtained composite material is CdZnSeS / ZnS quantum dots with A3 connected on the surface.

[0157] Material Example 6

[0158] The scheme of this embodiment is basically the same as that of Embodiment 1, with the only difference being that in this embodiment, in step (ii): the quantum dots are changed to CdSe quantum dots; accordingly, the prepared composite material is CdSe quantum dots with A3 connected on the surface.

[0159] Material Example 7

[0160] The scheme of this embodiment is basically the same as that of Embodiment 1, with the only difference being that, in this embodiment, in step (ii), the quantum dots are changed to CdSe / CdS / ZnS quantum dots; accordingly, the prepared composite material is CdSe / CdS / ZnS quantum dots with A3 connected to the surface.

[0161] Material Example 8

[0162] The scheme of this embodiment is basically the same as that of Embodiment 1, with the only difference being that, in this embodiment, in step (ii): the quantum dots are changed to CdSe / CdS / ZnCdS / ZnS quantum dots; accordingly, the prepared composite material is CdSe / CdS / ZnCdS / ZnS quantum dots with A3 connected on the surface.

[0163] Material Example 9

[0164] The scheme of this embodiment is basically the same as that of Embodiment 1, with the only difference being that, in this embodiment, in step (ii): the quantum dots are changed to CsPbBr3 quantum dots; accordingly, the prepared composite material is CsPbBr3 quantum dots with A3 connected on the surface.

[0165] Material Example 10

[0166] The scheme of this embodiment is basically the same as that of embodiment 3, except that, in this embodiment, the ligand raw material is undecadienylphosphonic acid; correspondingly:

[0167] In step (1), the product obtained by replacing eicosapentaenoic acid with linoleic acid (CAS 60-33-3) is (10Z, 12Z)-octadecane-9,12-dienethio-S-acid, and its nuclear magnetic resonance data are as follows: 1H NMR (500MHz, Chloroform-d) δ 5.43-5.32 (m, 4H), 2.66 (ddddq, J = 5.6, 4.3, 3.3, 2.1, 1.1 Hz, 2H), 2.56 (t, J = 7.3 Hz, 2H), 2.08-2.00 (m, 4H), 1.64 (p, J = 7.2 Hz, 2H), 1.40-1.20 (m, 14H), 0.93-0.86 (m, 3H). The H of the thiocarboxylic acid functional group -(C = O) SH is an active hydrogen, and there may be no signal in deuterated chloroform. The structure is shown in A9.

[0168] The composite material prepared in step (ii) is CdSe / ZnS quantum dots with A9 connected on the surface.

[0169] Material Comparative Example 1

[0170] The comparative example is core-shell quantum dots CdSe / ZnS (purchased from Sigma-Aldrich), which has a light emission wavelength of 580 nm and has oleic acid ligands connected to the surface.

[0171] Material Comparative Example 2

[0172] The scheme of this comparative example is basically the same as that of Example 10, except that in this comparative example:

[0173] Omit step (1);

[0174] In step (ii): the ligand raw material is changed to oleic acid, CAS 112-80-1; accordingly, the obtained composite material is CdSe / ZnS quantum dots with (10Z)-octadecene-9-thio-S-acid connected on the surface. Its nuclear magnetic data are as follows: 1H NMR (500MHz, Chloroform-d) δ5.37-5.30 (m, 2H), 2.56 (t, J = 7.3Hz, 2H), 2.02 (tq, J = 7.1, 3.5Hz, 4H), 1.64 (p, J = 7.2Hz, 2H), 1.36-1.23 (m, 20H), 0.94-0.85 (m, 3H). The H of the thiocarboxylic acid functional group - (C = O) SH is an active hydrogen, and there may be no signal in deuterated chloroform.

[0175]

[0176] Material Comparative Example 3

[0177] The scheme of this comparative example is basically the same as that of Example 10, except that in this comparative example:

[0178] Omit step (1);

[0179] In step (ii): the ligand raw material is changed to conjugated (10E, 12Z)-linoleic acid, CAS 2420-56-6; accordingly, the prepared composite material is CdSe / ZnS quantum dots with (10Z, 11E)-octadecadienylthio-S-acid connected on the surface. Its NMR data are as follows: 1H NMR (500MHz, Chloroform-d) δ6.02-5.93 (m, 1H), 5.76-5.64 (m, 2H), 5..56 (dddt, J = 10.4, 5.6, 4.9, 0.9 Hz, 1H), 2.56 (t, J = 7.3 Hz, 2H), 2.19-2.08 (m, 4H), 1.64 (p, J = 7.2 Hz, 2H), 1.45-1.22 (m, 16H), 0.94-0.85 (m, 3H). The H of the thiocarboxylic acid functional group - (C = O) SH is an active hydrogen and may have no signal in deuterated chloroform.

[0180]

[0181] Material Comparative Example 4

[0182] This comparative example is a core-shell quantum dot CdZnSeS / ZnS, and an oleic acid ligand is connected to the surface.

[0183] Material Comparative Example 5

[0184] This comparative example is a single structure quantum dot CdSe, and an oleic acid ligand is connected to the surface.

[0185] Material Comparative Example 6

[0186] This comparative example is a core-shell quantum dot CdSe / CdS / ZnS, and an oleic acid ligand is connected to the surface.

[0187] Material Comparative Example 7

[0188] This comparative example is a core-shell quantum dot CdSe / CdS / ZnCdS / ZnS, and an oleic acid ligand is connected to the surface.

[0189] Material Comparative Example 8

[0190] This comparative example is a core-shell quantum dot CsPbBr3 quantum dot, and an oleic acid ligand is connected to the surface.

[0191] Device Example 1

[0192] (1) Provide an ITO anode, wipe the ITO surface with a cotton swab dipped in a small amount of soapy water to remove impurities visible to the naked eye, then ultrasonically clean it with deionized water, acetone, anhydrous ethanol, and deionized water for 20 minutes, and then blow dry it with nitrogen for later use.

[0193] (2) Spin coating the PEDOT:PSS material on the anode at a rotation speed of 3000 rpm for 30 seconds and annealing at 100° C. for 10 minutes to obtain a hole injection layer with a thickness of 100 nm.

[0194] (3) The surface of the hole injection layer was spin-coated with TFB chlorobenzene solution at a speed of 3000 r / min for 30 s and annealed at 200° C. for 30 min to obtain a hole transport layer with a thickness of 70 nm.

[0195] (4) The composite material solution prepared in Example 1 was spin-coated on the hole transport layer at a rotation speed of 3000 rpm for 30 seconds and annealed at 80° C. for 30 minutes to obtain a light-emitting layer with a thickness of 20 nm.

[0196] (5) Spin-coat a ZnO ethanol solution on the light-emitting layer at a rotation speed of 3000 rpm for 30 seconds and anneal at 80° C. for 30 minutes to obtain an electron transport layer with a thickness of 40 nm.

[0197] (6) The wafer prepared in step (5) is placed into a vacuum coating machine, and an electrode is evaporated using a Ag target to obtain a cathode with a thickness of 60 nm, and then heat-treated at 120° C. for 15 min to obtain a QLED device.

[0198] Device Examples 2 to 10

[0199] The schemes of device embodiments 2 to 10 are basically the same as device embodiment 1, with the only difference being that in device embodiment n, in step (4), the composite material solution used is the composite material solution prepared in material embodiment n, where n is any integer from 2 to 10.

[0200] Device Comparison Examples 1 to 8

[0201] The schemes of device comparative examples 1 to 8 are basically the same as device embodiment 1, except that in device comparative example m, in step (4), the composite material solution used is the composite material solution prepared from material comparative example m, and m is any integer from 1 to 8.

[0202] Experimental example

[0203] (I) Take the thin films prepared from the material examples and the material comparison examples, and test the film-forming properties and fluorescence quantum yield stability of the thin films. The results are recorded in Table 1.

[0204] Preparation of quantum dot film: spin-coat the composite material solution on a glass substrate and solidify to form a quantum dot film.

[0205] The film forming property is detected by using an atomic force microscope (AFM) to detect the surface roughness of the film.

[0206] The method for detecting the stability of fluorescence quantum yield is as follows: placing the film under visible light environment, detecting its fluorescence quantum yield (PLQY) at 0 day and 14 days of exposure, respectively, and calculating the PLQY stability according to the following formula.

[0207] PLQY stability = PLQY at 14 days of exposure / PLQY at 0 days of exposure × 100%;

[0208] Among them, the fluorescence quantum yield (PLQY) detection method is: put the film into the built-in integrating sphere of the Edinburgh spectrometer to compare the incident photons with the photons emitted by the quantum dot solution.

[0209] Table 1

[0210]

[0211]

[0212] From the table above we can see that:

[0213] Material Examples 1 to 4 and Material Example 10 have lower surface roughness and PLQY change rate than Material Comparative Examples 1 to 3. Correspondingly, when comparing Material Comparative Examples 4 to 8 and Material Examples 5 to 9, the Material Examples have lower surface roughness and PLQY change rate than the Material Comparative Examples, indicating that the composite material proposed in the present application has better film-forming effect and better stability.

[0214] (ii) The devices prepared in the above device embodiments and device comparison examples were subjected to life tests and luminous efficiency tests.

[0215] Life test refers to the time taken for the device brightness to decay to a certain percentage of the maximum brightness under 2mA constant current drive. The time taken for the brightness to decay to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the life test cycle, the device life test is usually carried out at high brightness by accelerating device aging, and the life at low brightness is obtained by fitting the decay fitting formula. For example, the life at 1000nits is recorded as T95 1000nits, and the calculation formula is:

[0216]

[0217] Among them, T95 L The lifespan under low brightness, generally 1000nits, T95 H is the lifespan under high brightness, that is, the measured lifespan, L H is the maximum brightness that the device is accelerated to, L L Generally it is 1000nits, A is the acceleration factor, which is 1.7.

[0218] The detection method of external quantum efficiency EQE is: the ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, the unit is %, which is an important parameter to measure the quality of electrophotoelectric devices. It can be obtained by measuring with EQE optical testing instruments. Among them, the voltage when the brightness of the device reaches 1nite is the turn-on voltage. The specific calculation formula is as follows:

[0219]

[0220] Among them, ηe is the light output coupling efficiency, ηγ is the ratio of the number of recombined carriers to the number of injected carriers, x is the ratio of the number of excitons that generate photons to the total number of excitons, KR is the radiation process rate, and KNR is the non-radiative process rate.

[0221] Test conditions: carried out at room temperature, air humidity is 30-60%.

[0222] Table 2

[0223]

[0224]

[0225] From the table above we can see that:

[0226] Device Examples 1 to 4 and 10 have higher brightness, T95@1000nits and EQE than device Comparative Examples 1 to 3, and device Examples 5 to 9 have higher brightness, T95@1000nits and EQE than device Comparative Examples 4 to 8, indicating that by connecting ligands with polyunsaturated bonds on the surface of quantum dots, it is helpful to reduce the transition barrier of carriers between quantum dots, between the hole transport layer and the light-emitting layer, and between the electron transport layer and the light-emitting layer, and improve the injection capacity of quantum dot holes and electrons, thereby improving the brightness of the QLED device, improving the carrier balance of the device, and thus extending the service life and EQE of the device;

[0227] Further, comparing device example 1 with device comparison example 3, device example 1 has higher brightness, T95@1000nits and EQE; this may be because the conjugated ligand has an extremely low transition barrier for carriers, and carriers spontaneously tend to stay in the quantum dot or migrate in the conjugated ligand. Even under a low electric field, they are more inclined to remain in the ligand rather than transition to another quantum dot ligand. Therefore, it is necessary to increase the QLED operating voltage and increase the electric field to drive the carriers to transition to adjacent quantum dots, which consumes additional energy and causes an imbalance in carrier injection, resulting in a decrease in brightness, T95@1000nits and EQE.

[0228] The composite materials and preparation methods thereof, light-emitting devices and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A composite material, characterized in that: The method comprises an inorganic semiconductor particle and a ligand connected to the inorganic semiconductor particle, wherein the raw material of the ligand has the following structural formula: R1-R2; Wherein, R1 is a substituted or unsubstituted C8-C24 unsaturated chain hydrocarbon group, said R1 contains two or more unsaturated bonds, and said substituted substituent includes one or more of C1-C5 alkyl, C1-C5 alkoxy, halogen, thiol, amino, phosphonic acid group, carboxyl, and thiocarboxylic acid group; R2 is a bonding group connected to the inorganic semiconductor particles.

2. The composite material according to claim 1, characterized in that In R1, there are N carbon-carbon single bonds between two adjacent unsaturated bonds, where N is an integer greater than or equal to 2; and / or, In said R1, said unsaturated bond is a carbon-carbon double bond; and / or, In the R1, the number of the unsaturated bonds is 3 to 6; and / or, The R2 is a mercapto group, an amino group, a carboxyl group, a phosphonic acid group or a thiocarboxylic acid group.

3. The composite material according to claim 1, characterized in that The R1 is selected from -(CH2) n1 (CH2CH=CH) n2 (CH2) n3 CH3, wherein n1 is greater than or equal to 0, n2 is 3 to 6, n3 is greater than or equal to 0, and n1+n3 is 0 to 10; and / or, The R2 is a phosphonic acid group or a thiocarboxylic acid group.

4. The composite material according to claim 3, characterized in that The raw material of the ligand is selected from compounds having a structure shown in any one of the following formulae (A1) to (A9):

5. The composite material according to claim 1, characterized in that In the composite material, the weight percentage of the ligand is 5 to 20%; and / or, The inorganic semiconductor particles include quantum dots, and the quantum dots include at least one of single-structure quantum dots, core-shell quantum dots and perovskite semiconductor materials; the material of the single-structure quantum dots, the core material of the core-shell quantum dots and the shell material of the core-shell quantum dots are respectively selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds; the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnS At least one of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, Pb At least one of SeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, Ga At least one of AlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n- 2NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2 + , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is selected from Cl - Br - ,I - At least one of .

6. A method for preparing a composite material, characterized in that: The following steps are involved: providing inorganic semiconductor particles, organic solvents and ligand sources; Mixing the inorganic semiconductor particles, the organic solvent and the ligand source to obtain a composite material, wherein the composite material includes inorganic semiconductor particles and ligands connected to the inorganic semiconductor particles; Wherein, the ligand source has the following structural formula: R1-R2, R1 is a substituted or unsubstituted C8-C24 unsaturated chain hydrocarbon group, the substituted substituent includes one or more of C1-C5 alkyl, C1-C5 alkoxy, halogen, thiol, amino, phosphonic acid group, carboxyl, thiocarboxylic acid group, and R1 contains two or more unsaturated bonds; R2 is a bonding group connected to the inorganic semiconductor particles.

7. The preparation method according to claim 6, characterized in that: The organic solvent comprises at least one of aromatic hydrocarbons, olefins, aromatic olefins, aromatic ethers, aromatic esters and C5-18 alkanes; and / or, The weight ratio of the inorganic semiconductor particles to the ligand is (4-7):1; and / or, In the step of mixing the inorganic semiconductor particles, the organic solvent and the ligand source, the temperature during the mixing is 15 to 50° C.; and / or, The ligand source is selected from compounds having a structure shown in any one of the following formulae (A1) to (A9):

8. A light-emitting device comprising an anode, a light-emitting layer and a cathode, characterized in that: The material of the light-emitting layer includes the composite material according to any one of claims 1 to 5, or includes the composite material prepared by the preparation method according to any one of claims 6 to 9.

9. The light emitting device according to claim 8, characterized in that: The cathode and the anode are independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS. The material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

10. A display device, characterized in that: Comprising the light emitting device as claimed in claim 8 or 9.